Pertanggungjawaban Pembuktian Pidana Terhadap Penyandang Disabilitas Pelaku Tindak Pidana Narkotika Sesuai Undang Undang No. 35 Tahun 2009 - Maltus Hutagalung; Micael Jeriko Damanik; David Kevin Sibuea (Universitas Sari Mutiara Indonesia, 2023)
This research was conducted using descriptive analytical research method, the approach method used is the legal approach and the conceptual approach.Data collection techniques were sourced from library research and field research at the and the Institute for compulsory reporting recipients (IPWL) of the Mari Indonesia Bersinar Drug Victim Rehabilitation Center, then the data was analyzed qualitatively. Based on the results of the study, it is known that the factors of drug abuse against persons with disabilities on the community environment is that the impact is very broad and is a serious threat to various aspects of life and survival of the nation and state. The efforts made by the in preventing and controlling narcotics are carrying out routine activities of GKN (Grebek Kampung Narkoba), conducting regular counseling in areas prone to narkoba, conductingmutual cooperation activities in drug-prone areas,developing the shining program (Drug Clean). Register yourself or the victim to the recipient Institution for Compulsory Reporting (IPWL) the Mari Indonesia Bersinar Drug Victim Rehabilitation Center as a place for recovery, immediately conduct socialization and education to the community so that this does not happen